Prevention of Epilepsy in Infants with Tuberous Sclerosis Complex in the EPISTOP Trial - Kotulska, Katarzyna; Kwiatkowski, David J; Curatolo, Paolo; Weschke, Bernhard; Riney, Kate; Jansen, Floor; Feucht, Martha; Krsek, Pavel; Nabbout, Rima; Jansen, Anna C; Wojdan, Konrad; Sijko, Kamil; et al. (Annals of neurology, 2021)
OBJECTIVE: Epilepsy develops in 70 to 90% of children with tuberous sclerosis complex (TSC) and is often resistant to medication. Recently, the concept of preventive antiepileptic treatment to modify the natural history of epilepsy has been proposed. EPISTOP was a clinical trial designed to compare preventive versus conventional antiepileptic treatment in TSC infants. METHODS: In this multicenter study, 94 infants with TSC without seizure history were followed with monthly video electroencephalography (EEG), and received vigabatrin either as conventional antiepileptic treatment, started after the first electrographic or clinical seizure, or preventively when epileptiform EEG activity before seizures was detected. At 6 sites, subjects were randomly allocated to treatment in a 1:1 ratio in a randomized controlled trial (RCT). At 4 sites, treatment allocation was fixed; this was denoted an open-label trial (OLT). Subjects were followed until 2 years of age. The primary endpoint was the time to first clinical seizure. RESULTS: In 54 subjects, epileptiform EEG abnormalities were identified before seizures. Twenty-seven were included in the RCT and 27 in the OLT. The time to the first clinical seizure was significantly longer with preventive than conventional treatment [RCT: 364 days (95% confidence interval [CI] = 223-535) vs 124 days (95% CI = 33-149); OLT: 426 days (95% CI = 258-628) vs 106 days (95% CI = 11-149)]. At 24 months, our pooled analysis showed preventive treatment reduced the risk of clinical seizures (odds ratio [OR] = 0.21, p = 0.032), drug-resistant epilepsy (OR = 0.23, p = 0.022), and infantile spasms (OR = 0, p < 0.001). No adverse events related to preventive treatment were noted. INTERPRETATION: Preventive treatment with vigabatrin was safe and modified the natural history of seizures in TSC, reducing the risk and severity of epilepsy. ANN NEUROL 2021;89:304-314.
Keywords: Anticonvulsants; Epilepsy; Seizures; novorozenec; Infant, Newborn; epilepsie; Infant; Humans; kojenec; tuberózní skleróza; antikonvulziva; Drug Resistant Epilepsy; Female; záchvaty; křeče u dětí; lidé; elektroencefalografie; vigabatrin; refrakterní epilepsie; ženské pohlaví; Male; Vigabatrin; Spasms, Infantile; Tuberous Sclerosis; Mass Screening; Electroencephalography; plošný screening; mužské pohlaví